2013
DOI: 10.1158/1055-9965.epi-13-0546
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Cigarette Smoking on the Survival of Patients with Established Nasopharyngeal Carcinoma

Abstract: Background: Cigarette smoking is associated with the etiology of nasopharyngeal carcinoma; however, the influence of smoking on survival in patients with established nasopharyngeal carcinoma remains unknown.Methods: We retrospectively analyzed 1,849 patients with nasopharyngeal carcinoma who were categorized as never, former, and current smokers. Cumulative effect of smoking was defined in terms of pack-years. Associations between cigarette exposure and survival were estimated by Cox proportional hazards model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…In addition to N-stage, age, gender and total radiotherapy doses, which are common prognostic factors in NPC [31], LDH, BMI and smoking are important baseline prognostic factors for tumour recurrence or distant metastasis. These findings are consistent with those presented in previous studies [13,14,32,33]. Currently, distant metastasis is the predominant pattern of failure in locoregionally advanced nasopharyngeal carcinoma [8].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to N-stage, age, gender and total radiotherapy doses, which are common prognostic factors in NPC [31], LDH, BMI and smoking are important baseline prognostic factors for tumour recurrence or distant metastasis. These findings are consistent with those presented in previous studies [13,14,32,33]. Currently, distant metastasis is the predominant pattern of failure in locoregionally advanced nasopharyngeal carcinoma [8].…”
Section: Discussionsupporting
confidence: 93%
“…BMI was defined as pre-treatment weight (kg) divided by the square of height (metres). Based on previous studies [13,14], smoking status at diagnosis was categorised into two groups: (i) never-smokers, which referred to patients who never smoked; and (ii) ex-smokers, which referred to former smokers who had stopped smoking and smokers who continued smoking until the day of hospitalisation. The cutoff values for Epstein-Barr virus (EBV) VCA-IgA and EA-IgA were set at 1:80 and 1:10, respectively, based on previous studies [15,16].…”
Section: Patients and Proceduresmentioning
confidence: 99%
“…As observed in our study, a higher percentage of diabetic patients were indeed smokers and overweight or obese. Additionally, according to recent studies, NPC patients with smoking history had poorer survival [32] whereas those with higher BMI had favorable survival [33] . Therefore, the contradictory effect of smoking and BMI maybe just right principally confounded the impact of FPG on survival of NPC.…”
Section: Discussionmentioning
confidence: 98%
“…One study reported that the effect of smoking was evident only among the chemoradiotherapy or radiotherapy group [37]; another, found that smoking status was the strongest predictor of survival, in both current and former smokers [38]; a third large population-based study from Ireland, involving 5652 patients with HNC, reported significantly increased cancer-related death rate for current smokers with oral cavity, pharyngeal, and laryngeal cancers, and the association was stronger in surgically treated patients [39]. Moreover, the association between cigarette smoking and survival has been demonstrated also in colon [40], pancreatic cancer [41], renal cell carcinoma [42], oropharyngeal [43], and nasopharyngeal carcinoma [44] highlighting a possible enduring effects of smoking, even after stopping. In our study, smoking status at diagnosis is not an independent prognostic factor of overall survival among patients with HNC.…”
Section: Discussionmentioning
confidence: 99%